2022
DOI: 10.21203/rs.3.rs-1389981/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Morphological And Molecular Variability Of Sporisorium Scitamineum Isolates In Eswatini

Abstract: Background: Sugarcane smut, caused by Sporisorium scitamineum, is a disease of economic importance in the sugarcane industry, occasioning losses of up to 50%. Current management practices have been shown to be ineffective in controlling the fungal disease and hence the understanding of the local pathogen and development of appropriate control measures is required. This study investigates the morphology, development patterns and molecular variability of Sporisorium scitamineum isolates in Eswatini to understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…The primary infection is caused by soil-borne teliospores or the planting of diseased setts, while secondary infection is caused by air-borne fungal spores infecting a healthy crop that is already standing (Hoy et al, 1991a). Nkhabindze et al (2022) reported that although there were morphological differences in isolates, the genetic variation among isolates for the Internal Transcribed Spacer (ITS) was very low.…”
Section: Pathogen Of Sugarcane Smut Diseasementioning
confidence: 99%
“…The primary infection is caused by soil-borne teliospores or the planting of diseased setts, while secondary infection is caused by air-borne fungal spores infecting a healthy crop that is already standing (Hoy et al, 1991a). Nkhabindze et al (2022) reported that although there were morphological differences in isolates, the genetic variation among isolates for the Internal Transcribed Spacer (ITS) was very low.…”
Section: Pathogen Of Sugarcane Smut Diseasementioning
confidence: 99%